2019
DOI: 10.1175/bams-d-19-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Our Skill in Modeling Mountain Rain and Snow is Bypassing the Skill of Our Observational Networks

Abstract: 17In mountain terrain, well-configured high-resolution atmospheric models are able to 18 simulate total annual rain and snowfall better than spatial estimates derived from in situ 19 observational networks of precipitation gauges, and significantly better than radar or 20 satellite-derived estimates. This conclusion is primarily based on comparisons with 21 streamflow and snow in basins across the Western United States and in Iceland, Europe, 22and Asia. Even though they outperform gridded datasets based on ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 176 publications
8
171
0
Order By: Relevance
“…The climatology in CM2.5, in terms of pattern and magnitude, seems to be more consistent with the EOBS dataset. However, due to a relatively large observational uncertainty in many mountainous areas leading to the underrepresentation of precipitation over complex terrain in gridded observational datasets, it is difficult to validate the model rainfall climatology in the region (Lundquist et al, 2019). The CM2.5 results are comparable to the downscaling simulations using high-resolution (at ∼ 50 and ∼ 12 km) regional climate models of the EURO-CORDEX experiment .…”
Section: Summer Mean Present Climate and Teleconnections Over The Medmentioning
confidence: 86%
See 1 more Smart Citation
“…The climatology in CM2.5, in terms of pattern and magnitude, seems to be more consistent with the EOBS dataset. However, due to a relatively large observational uncertainty in many mountainous areas leading to the underrepresentation of precipitation over complex terrain in gridded observational datasets, it is difficult to validate the model rainfall climatology in the region (Lundquist et al, 2019). The CM2.5 results are comparable to the downscaling simulations using high-resolution (at ∼ 50 and ∼ 12 km) regional climate models of the EURO-CORDEX experiment .…”
Section: Summer Mean Present Climate and Teleconnections Over The Medmentioning
confidence: 86%
“…In the summer, the northward shift of the Hadley cell reveals a connection between the hot and arid eastern part of the Mediterranean and the Asian and African monsoons, as well as a possible connection between these two monsoons (Rodwell and Hoskins, 1996;Ziv et al, 2004;Fontaine et al, 2011;Raicich et al, 2003;Rowell, 2003). The thermal balance of the central-eastern part of the Mediterranean is largely maintained by the two dynamical factors, i.e., the cool air advection of the low-level northerly winds (i.e., Etesians; HMSO, 1962;Metaxas, 1977;Maheras, 1980;Prezerakos, 1984;Reddaway and Bigg, 1996;Zecchetto and de Biasio, 2007;Chronis et al, 2011) and the adiabatic warming of the mid-and upper-level subsidence winds (Raicich et al, 2003;Mariotti et al, 2002;Tyrlis et al, 2013), which counterbalance each other. Ziv et al (2004) have shown these two factors to be significantly correlated, pointing to the Asian summer monsoon, which exerts an influence on the Mediterranean surface, middle, and upper troposphere dynamics.…”
Section: Introductionmentioning
confidence: 93%
“…Much work has been done to compare WRF-simulated precipitation to both in situ and gridded datasets (Caldwell et al, 2009;Leung and Qian, 2009;Qian et al, 2010;Gutmann et al, 2012;Cardoso et al, 2013;Warrach-Sagi et al, 2013), and the consensus is that WRF estimates are reasonably skilled at capturing realistic precipitation patterns and magnitudes (Hughes et al, 2017). Recent work suggests that atmospheric models such as WRF provide better estimates of precipitation in mountainous regions than precipitation gauge networks (Lundquist et al, 2019); known errors in observational networks pose major challenges to validating climate simulations. Therefore, we do not aim to evaluate WRF-simulated precipitation in this work and instead focus on precipitation changes throughout the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the representation of orographic forcing also improves simulations of extreme precipitation in mountains, such as that induced by atmospheric rivers (e.g., Leung and Qian 2009;Chen et al 2018). In fact, in mountainous regions, well-configured regional models may produce better estimates of total annual rain and snow than current observational estimates (Lundquist et al 2019) and improve understanding of processes driving surface hydrologic extremes associated with landfalling atmospheric rivers in mountainous areas (Chen et al 2019).…”
Section: E674mentioning
confidence: 99%